Yutthasāt læ māttrakān nai kānsongsœ̄m krabūankān rīanrū khō̜ng dek nai radap thō̜ngthin (Samnak Songsœ̄m læ Phithak Dek, Samnakngān Songsœ̄m Sawatdiphāp læ Phithak Dek, Yaowachon, Phūdō̜i ʻŌkāt, Khonphikān, læ Phūsūngʻāyu, Krasūang Kānphatthanā Sangkhom læ Khwāmmankhong khō̜ng Manut, 2009)
Strategies and criteria in the promotion of learning process of children in localities throughout Thailand.